PREVALENCE OF PHYSICAL AND PSYCHOLOGICAL FORMS OF CHILD ABUSE: IMPLICATION FOR INTERVENTION, GONDAR, NORTH WEST ETHIOPIA. - Sewasew, Daniel Tsehay; Mengiste, Messaye Mulatie (Innovare Journal of Social Sciences, 2014)
Abstract Introduction: The purpose of this study was to describe/determine prevalence of physical and psychological forms of child abuse in some selected elementary schools in North Gondar.Â Â Methods: Three hundred twenty one children whose age ranges from seven to seventeen years were randomly drawn from four schools through simple random sampling technique using lottery method. In this study, questionnaire was used to gather data from students. Â Results: Most children faced physical abuse in the form kicked with an object (73.8 %), Pinching (78.5 %) and slapping on head (70.73%). There was statistically significant difference between male and female children being victim of form kicked with an objectÂ (Ï‡2=72.9, df=1, p<0.05), Â Pinching (Ï‡2=28.1, df=1, p<0.05) andÂ slapping on head(Ï‡2=55.1, df=1, p<0.05). Male children were more victims of these types of physical abuse as compared to female children. Moreover, substantial proportions of children were suffering from psychological abuse through terrorising in the form of threatening with severe punishment (64.8%) and threatening to leave home (57%). Furthermore, sizeable proportion of children faced psychological abuse in the form of being seen as worthless/useless by parent/caregiver (53.9%) and negative comments by comparing with others (62.1%). There was statistically significant difference between male and female children in psychological abuse in the form of being threatened with severe punishment (Ï‡2=28.15, df=1, p<0.05) and in name calling (Ï‡2=7.48, df=1, p<0.05). More proportion of boys experienced threatening with severe punishment and name calling as compared girls. Therefore, prevention efforts and policies should address physical and psychological abuse. Â Key terms: Prevalence, Physical Abuse, Psychological Abuse, Child Abuse